Dampak Modernisasi Terhadap Sistem Pertanian Berbasis Tri Hita Karana di Desa Bugbug Karangasem-Bali - Muhadir, Octawinanda; Murniasih, A.A.Ayu (Humanis, 2018)
The essentially of Tri Hita Karana is a relationship built between human to the god, human to human and human to the nature. These three aspects are inseparable elements, and also inherent to the agricultural system in the Bugbug village. That’s three relationship is purpose to create a harmonious life. However, the elements of modernization entering into the life of the community in Bugbug village and causing some impact. This research is interesting to be investigated further with the formulation of the problem (1) How is the agricu l ture system based T ri H ita K arana in the Bugbug village and, (2) What is the impact of modernization on agricultural system based Tri Hita Karana in Bugbug village. As the purpose of this research is to know the system of agriculture based Tri Hita Karana in Bugbug village and to know the impact of the modernization of Tri Hita Karana based agriculture system in Bugbug village. The theory used is the theory of modernization by J.W Schoorl. The conculsion of this research is first, the agriculture system in the Bugbug village is categorized as a agriculture based Tri Hita Karana because the people still pay attention to the pattern of relationship between parhyangan, pawongan and palemahan aspect. Second, the entry of modernization elements into agriculture system based Tri Hita Karana raises a number of impact that divided into three aspects parhyangan, pawongan and palemahan.